Death contemplation and mental well-being in elderly Thai Buddhist meditation practitioners - Glushich, Alla; DeMaranville, Justin; Wongpakaran, Tinakon; Wedding, Danny; Wongpakaran, Nahathai (Narra Sains Indonesia, 2025)
Depression is prevalent among older adults in Southeast Asia, with fear of death as a key contributing factor. In Thailand, Buddhist death contemplation practices promote acceptance of mortality and may support mental well-being. However, their impact on mental health among elderly Thai Buddhist meditation practitioners remains underexplored. The aim of this study was to examine the interrelationships among death contemplation practice, positive death attitudes, and key psychological outcomes: well-being, depression, and gratitude among elderly Thai Buddhist meditation practitioners. A cross-sectional study design was employed, and data were collected from elderly Thai Buddhist meditation practitioners in Northern Thailand. Participants completed validated instruments assessing death attitudes (Morana Questionnaire; MoQ), death contemplation practice (Modified Meditation Evaluation Questionnaire; MMEQ), well-being (WHO-5-T), depression (Outcome Inventory-21), and gratitude (Gratitude Inventory-6). Descriptive statistics, Pearson correlations, and analysis of covariance (ANCOVA) were used to examine associations among variables and differences across levels of death contemplation practice. A total of 332 elderly participants (mean age=68.12 years; 66% female) were included. Death contemplation practice showed a significant negative association with depression (p=0.011) but not with well-being (p=0.116) or gratitude (p=0.226) after controlling for covariates. Positive death attitudes were independently associated with lower levels of depression (p<0.001), as well as higher levels of well-being (p<0.001) and gratitude (p<0.001), remaining a significant predictor across all outcomes. The association between contemplation and depression weakened when positive attitudes were included in the model, suggesting a mediating effect. These findings underscore the central role of positive death attitudes, cultivated through contemplative practice, in supporting mental health among elderly Thai Buddhist meditation practitioners. Integrating such practices into interventions may offer culturally appropriate strategies for enhancing well-being in aging Buddhist populations.